The Palgrave handbook of the European administrative system - Bauer, Michael W. 1969-; Trondal, Jarle (Palgrave Macmillan, 2015)
"This important collection examines the emerging bureaucratic framework which underpins the European Union and in doing so constitutes a primer on the administrative system of the EU. Drawing on the latest research from the administrative sciences and using organizational, institutional and decision-making theories, this volume highlights that analyzing the patterns and dynamics of the administrative capacities of the EU are essential in understanding how the EU shapes European public policy. Accordingly, this study does not examine administrative capacities not in isolation but rather analyzes them as structures that mobilize systematic bias in the production of public policy. This layout allows the chapters to tackle pressing questions about the nature of the EU's emerging bureaucracy such as to what extent, how and under what conditions do administrative systems change and complement pre-existing public administration systems? Can new administrative systems profoundly transform pre-existing ones? And What are the principled implications of an emergent new European administrative system? "..
Keywords: Europäische Union; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Government / International; Politik; Public administration -- European Union countries; Administrative agencies -- European Union countries; Bureaucracy -- European Union countries; Verwaltung; Europäische Union. Mitgliedsstaaten; European Union countries -- Politics and government; Aufsatzsammlung